Informações biológicas e estimativa do tamanho ideal da colmeia para a abelha tiúba do Maranhão (Melipona compressipes fasciculata Smith - Hymenoptera, Apidae) - Kerr, Warwick Estevam (2001)
Four places in Latin-America have Melipona Illiger, 1806 beekeeping: Mexico, with M. beecheii Bennet, 1831; Northeast Brasil, with M. scutellaris Latreille, 1811; Maranhão State (Brazil) with M. compressipes fasciculata Smith, 1854; Venezuela, in her coast, with M. favosa (Fabricius, 1798). Natural colonies of M. compressipes fasciculata occupied tree holes ranging from 6,5 to 24 1. The average honey production of 60 colonies in hives with capacity of 50.2 1, 41.0, 30.2, 16.5 and 6.2 were respectively 8.4, 6.5, 5.5, 3.3 and 2.0 Kg. Due to lack of bee flowers within the city limits, hives with a volume of 27 1 (30x30x30 cm) were used successfully in our future experiments with M. compressipes fasciculata instead of the ideal size of 40 to 50 liters, since the intense use of biological material did not allow the colonies to reach large sizes.